Diabetes mortality and trends before 25 years of age: an analysis of the global burden of disease study 2019 (2022)
Diabetes has been identified by the UN and WHO as one of the five priority non-communicable diseases (NCDs) in their Action Plan to confront the NCDs challenge.1, 2 Prevention and management of the chronic complications in patients with diabetes involve complex, long-lasting, and costly endeavours.3 By contrast, deaths due to acute complications (ie, diabetic ketoacidosis, hyperosmolar coma, and severe hypoglycaemia), early-onset renal failure, and acute infections can be prevented through a minimal core set of actions. These include the provision of affordable insulin,4 access to health care (including glucose monitoring and promptly available services for acute decompensation), and health education (including rapid recognition and detection of type 1 diabetes and ketoacidosis).5 Since contemporary health care in high-income countries6, 7, 8 has proven to be effective in reducing mortality due to these complications it is reasonable to assume that major reductions could be seen globally if better care, including the availability of affordable insulin, were more widely provided. Many low-income and middle-income countries (LMICs) have made considerable progress in the provision of a minimal core of actions to prevent mortality due to acute complications of diabetes. For example, Brazil observed a decrease of 74·5% in deaths due to acute complications in people younger than 40 years from 1991 to 2010 following the implementation of the National Health System, which greatly increased access to care for patients with diabetes, including the provision of free insulin.9 Since mortality data are the most available health statistics worldwide, they can be used to track levels and trends in basic care for diabetes. However, deaths due to diabetes (International Classification of Diseases, revision 10 [ICD-10], codes E10–E14) are frequently further classified vaguely as due to multiple (.7) or unspecified (.8) complications, or without complications (.9), making a direct assessment of trends in deaths due to acute complications difficult.10 For example, from 1996 to 2011 in Brazil, 83·6% of deaths, after removing those due to renal disease (.2) and peripheral arterial disease (.5), were coded with uninformative .7 to .9 codes.10 However, because mortality in people younger than 25 years is probably mostly due to acute complications,11 restricting the evaluation to this age range permits a focus on avoidable causes of death.